Atmospheric aerosol and black carbon optical properties and associated radiative forcing under haze conditions. (January 2021) - Zhang, Ming; Fan, Ruonan; Ma, Yingying; Gong, Wei; Shi, Yifan
Highlights: We studied BCRF in ultraviolet, visible, and near-infrared spectra under haze. ARF and BCRF increase with the development of haze. Radiative forcing efficiency is weakened by increased forward scattering. Abstract: The optical properties and radiative forcing of atmospheric aerosol (ARF) and black carbon (BC) aerosol (BCRF) in ultraviolet (UV), visible (VIS), near-infrared (NIR), and shortwave (SW) spectra were investigated under haze conditions based on the observations of the Aethalometer and sun-sky radiometer and simulations from libRadtran. The results show that the BC concentrations increased greatly from 2.73 μg/m 3 under clear-air conditions to 7.95 μg/m 3 under severe haze conditions, while BC aerosol optical depth (AOD) increased from 0.025 to 0.092. A high correlation (R 2 =0.62) was found between BC AOD and absorbing aerosol optical depth (AAOD) derived from the sun-sky radiometer. The BCRF in SW (BCRFSW ) varied from -10.20 W/m 2 under clear-air conditions to -25.40 W/m 2 under severe hazy conditions. However, its fraction in ARF (ARFSW ) decreased from 19% to 17% simultaneously, which is mainly related to the decrease of the ratio of BC AOD to AOD. The fraction of ARF in VIS in ARFSW decreased from 56.3% under clear-air conditions to 50.5% under severe haze conditions, while the fraction of BCRF in VIS in BCRFSW was much larger, and increased from 72.9% to 73.8%. The BCRF efficiency (BCRFE) was much larger than ARF efficiency (ARFE), and both of them decreased with the development of haze. The ARFE in SW decreased from -173.84 W/m 2 under clear-air conditions to -112.75 W/m 2 under severe haze conditions while BCRFESW varied from -482.50 W/m 2 to -321.88 W/m 2 . The decrease of ARFE and BCRFE is related to the increase of aerosol loading and asymmetry factor (ASY). The ASY increased and the forward scattering was enhanced with the development of haze due to the hygroscopic growth of aerosol particles, which reduced the extinction efficiency of aerosols including BC on solar radiation and the cooling effect on the surface.